THE EFFECT OF COW AND SOY MILK CONSUMPTION ON CALCIUM LEVELS OF WISTAR RAT TEETH - Ahassa, Ulya; Wardani Mahendra, Putri Kusuma; Soeprihati, Indah Titien (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Complementary food (MPASI) is the main food after the child weans from exclusive breastfeeding. One of the main sources of complementary food is milk. Most children are fed with cow’s milk, but since some children are lactose intolerant, they will be recommended to consume soy milk. However, soy milk and cow’s milk are known to have different amount of calcium as one of the key nutrients for tooth growth and development. The purpose of this study was to compare the effect of cow’s milk and soy milk consumption on the calcium concentration of Wistar rat teeth.Method: Subjects were 27 male Wistar rats aged 1 month old divided into 3 groups, equally with 9 rats in each: groups that consumed cow’s milk, soy milk, and control group. The group consuming Cow and soy milk was fed 2 times a day, in the morning and evening for 28 days. Each subject was then euthanized and their mandibular right incisor was taken at the end of the treatment to measure calcium concentration by atomic absorption spectrophotometry.Result: The results of the one way ANOVA test showed that there were significant differences (p <0.05) in the calcium concentration of incisors in the teeth of rat consuming cow’s milk, soy milk, and control group. Hence, it can be concluded that the consumption of cow’s milk and soy milk has an effect on the calcium concentration of Wistar rat teeth. Conclusion: Calcium concentration of Wistar rat teeth that consume cow’s milk is higher than those that consume soy milk.